Statistical Distribution of Urban Area Reveals a Converging Trend of Global Urban Land Expansion - Shengjie Hu; Zhenlei Yang; Sergio Andres Galindo Torres; Zipeng Wang; Haoying Han; Yoshihide Wada; Thomas Cherico Wanger; Ling Li (Earth's Future)
Abstract Urban land expansion is a major driver of many environmental and societal changes that challenge human well‐being and sustainable development, but its evolutionary process and dynamics are neither clear nor well‐integrated into urban science quantitatively. We analyzed the global urban extent data based on nighttime lights to examine the statistical distribution of urban land area at the global scale, and in 13 regions and countries over 29 years. The results reveal a converging temporal trend in urban land expansion from subnational to global scales, characterized by a coherent shift of urban area distribution from an initial power law toward an exponential distribution. This trend is well captured by a unified mathematical model based on the shifted power law distribution function and is reflected in the gradual predominance of medium‐size cities over small‐size cities in the configuration of urban systems across the world. The shift of urban area distributions bears the consequence of reduced urban system stability and resilience, and can be linked to increasing exposure of urban populations to extreme heat events and air pollution. These changes are likely to be driven by the increasing influence of external economies of scale associated with globalization. The findings challenge the status quo of land urbanization practices and emphasize the importance of medium‐size cities in urban planning.